IMPLEMENTASI DATA MINING UNTUK PENGELOMPOKKAN WILAYAH PELANGGARAN LALU LINTAS MENGGUNAKAN METODE K-MEANS PADA POLRES BENGKULU - Devi Sartika; Juju Jumadi (Smart Education, 2023)
Numbers of congestion and especially traffic violations occur everywhere in the city of Bengkulu, especially at city junctions. The large number of road users who do not comply with traffic regulations properly, every day can increase the rate of accidents and violations of traffic rules in driving in the Bengkulu City area. Due to the large piles of data on traffic violations in the jurisdiction of the Bengkulu City Police, each year only this data is processed into Microsoft Excel, making the data irregular. The process of extracting useful information in order to obtain violation data can be carried out using data mining methods, one of which is k-means clustering The implementation of the system uses the Visual Basic 2010 programming language. From the results of the tests conducted, it can be concluded that the areas with the most violations are the Tanah Patah and Betungan areas, for areas with violations in the moderate group there are Sawah Lebar, Pintu Batu, Padang Harapan, Kebun Tebeng and Simpang Nakau and for areas with low violations are the Swamp Makmur and Sungai Hitam areas